FAKTOR FINANSIAL DAN NON FINANSIAL YANG MEMPENGARUHI AGRESIVITAS PAJAK DI INDONESIA - Ardy .; Ari Budi Kristanto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
Tax aggressiveness conveys benefit in promoting tax payers’ efficiency, but alsobringing the risk at once. The efficiency can be reached through minimizing the tax payment. On the other hand, tax payers’ reputation and firm value may be weakened if the tax aggressiveness is put into opportunistic objective. This paper aims to investigate whether the financial and non-financial factors influence the tax aggressiveness. Financial factors comprise leverage and liquidity. Moreover, the nonfinancial factors cover the proportion of independent commissioners, audit committee and family ownership. Furthermore, the tax payers’ aggressiveness is measured by Effective Tax Rate. The research formulates five hypotheses which are tested using linear regression methods. Moreover, this research employs 72 firm years as samples, which covermanufacturing companies listed in the Indonesian Stock Exchange during 2010 until 2013. Those samples are sorted out by purposive sampling method. The samples are chosen using the purposive sampling method based on certain designated criterias. The result shows that financial factors consist of leverage and liquidity, and nonfinancial factor of audit committee positively influences the tax aggressiveness. While the proportion of independent commissioners and family ownership do not have significant influence toward tax aggressiveness. This finding implies that Indonesian companies tend to aggressive in avoiding the tax for the financial motives rather than non financial motives.Keywords: leverage, liquidity, independent commissioners, audit committee, family ownership, tax aggressiveness